in the following expression: x-(21*x\100)=275000 how does that become x=27500000\79?

Guest Mar 22, 2014

#1**0 **

What I want someone to do is show me the work. The web2.0calc.com is great for solving the problem, but I'd like to understand the process--in other ways see all the steps.

Guest Mar 22, 2014

#2**0 **

Hello, lets start:

*x-(21x/100) = 275000* => Now we just subtract x from the fraction 21x/100. Here's how: __http://www.mathsisfun.com/fractions_subtraction.html__

And we got =>

[list]*(100x-21x)/100 = 275000* => *79x/100 = 275000* =>[/*:m][/list:u]

Now we multiply with 100 from both sides:

[list] => *100 * (79x/100) = 100 * 275000* => *79x=27500000*[/*:m][/list:u]

Then, we divide with 79 from both sides:

[list] => *79x/79 = 27500000/79* => **x = 27500000/79**[/*:m][/list:u]

If you need more help, you can reply here

Dms

geofjen@gmail.com:in the following expression: x-(21*x\100)=275000 how does that become x=27500000\79?

Hello, lets start:

And we got =>

[list]

Now we multiply with 100 from both sides:

[list]

Then, we divide with 79 from both sides:

[list]

If you need more help, you can reply here

Dms

Dms Mar 22, 2014